The role of the IMF in addressing climate change risks (European Central Bank (ECB), 2022)
Climate change poses three specific but interrelated policy challenges: climate change mitigation, climate change adaptation (which includes building up resilience) and managing transition risks. The International Monetary Fund (IMF) is a multilateral institution with global reach and near-universal membership. Therefore, along with other international organisations, it has an important role to play in addressing the policy challenges posed by climate change. This paper discusses the contribution the IMF makes and can make in its three areas of competence: surveillance, lending and technical assistance. The paper concludes that the IMF has significantly increased its engagement in climate change matters in recent years but should further intensify its efforts in ways that are fully consistent with its mandate.
Keywords: F3; F33; F34; O19; Q5; Q48; Q54; 330; International Monetary Fund; climate change; surveillance; lending; technical assistance